The advantages of using photonic crystal fibers in telecommunication systems - Haider Ali Muse (ХНУРЭ, 2016)
Photonic crystal fibers provide better than any other transmission bandwidth and are now the transmission medium of choice for long distance in telecommunication systems. The development of all optical communications can benefit from the index guiding photonic crystal fibers, conventional optical fibers have within the last decades revolutionized the communications industry and it is today a mature technology being pushed to its limit with respect to properties such as losses, single mode operation and dispersion. In this paper we will discuss the benefit of using photonic crystal fibers in telecommunication systems
Keywords: photonic crystal fiber; telecommunication system; optical communication